Exploring Multicultural Picturebooks in a Heritage Language Classroom - Chaehyun Lee (CLELEjournal, 2021)
The context of this study is a Korean heritage language school classroom in the United States. With Exploring Multicultural Picturebooks in a Heritage Language Classroom, Chaehyun Lee explores using multicultural literature with a class in the third grade. The findings of her study have implications particularly for educators of culturally and linguistically diverse children.